Rempah dan Kosmopolitanisme Islam: Koneksi Spiritual-Intelektual Palembang, Banten dan Demak dibalik Perdagangan Global Abad XV-XVI - Wahyudi, Johan; Suaedy, Ahmad (Faculty of Islam Nusantara, Nahdlatul Ulama University of Indonesia (Unusia) Jakarta., 2022)
Nusantara is known as the world's main supplier of spices since classical times. Various spices such as pepper, nutmeg and cloves are excellent in the international market. Studies on Indonesian spices, as conducted by Wellan, OW Wolters, J.C. Van Leur, Chalwani Michrob to Fahmi Irfani show a map of the important pepper trade in Sumatra and Java. It should be noted that the spice trade network is also related to the spiritual contact between Islam and Hindu-Buddhist teachings or local beliefs. This can be seen traces in Palembang, Banten and Demak. By using the historical method armed with a socio-economic approach, a number of historical explanations can be found. The author uses an explanation model by looking at the function of the port on the coast, its relation to trade routes in the interior. The purpose of writing this article is to present a new study for the historical discourse of Islam Nusantara. As is well known, seas, lakes, rivers and various watery inlets, both dynamic and static, are not a barrier to human interaction in the archipelago. In addition to the commercial aspect, which has been widely reviewed by a number of previous researchers, there is other information that has not been discussed, namely the existence of a spiritual-intellectual network that is connected between one area and another. The author finds a number of interesting facts, such as the emergence of the discourse of Islamic cosmopolitanism which is the result of a dialogue between immigrant and coastal communities. For example, in the case of the establishment of the Palembang Sultanate, Ki Gede ing Suro, a political figure from Demak, built a mosque near the Kutogawang Palace as a locus of Islamic education for the local population. There are findings in the form of the distribution of Ilmu Kebal (similar to Ilmu Pancasona) which was inherited by Arya Penangsang from Jipang Panolan, Central Java, to his descendants who are believed to still exist in the Mount Batu, Komering. This cross-island relationship is an important finding that confirms that in the XV-XVI centuries, cross-island intellectual spiritual contacts have been found in the archipelago. This article is the result of research on cities and intellectual networks in Palembang, Banten and Palembang funded by the Ministry of Religion of the Republic of Indonesia.